Problematika Pembelajaran Kitabah dan Tarjamah di Madrasah Ibtidaiyah - Nanik Setyowati (Study Program of Arabic Language Teaching, 2020)
The Arabic language is one of the competencies that must be mastered by the elementary school (Madrasah Ibtidaiyah/MI) students. However, in the course of learning Arabic, there are still various learning problems, especially in writing and translating Arabic. Speaking about the problem of learning Arabic, which was the object of research, the writers hoped to solve that problem or at least could reduce the gap. This study aimed to describe the learning patterns of writing skills and the ability to translate Arabic in MI, problems and find the right solution to support the learning of writing skills and the ability to translate Arabic in MI involving all components in the school, namely teaching materials, teachers, the principal's learning and policy process. This research is a qualitative study using descriptive-qualitative methods. The data used include two things, namely primary data and secondary data. Data collection technique was in the form of documentation. The researchers were trying to collect data relevant to learning Arabic in MI systematically, which were then analyzed by theory. The data analysis technique used grounded research in which the researchers analyzed the data and existing problems with the theory used. This research takes focus on the students of Class V Madrasah Ibtidaiyah Al-Jihad Karanggebang Jetis Ponorogo. Based on the data analysis, it was concluded that learning to write and translate Arabic in MI had been going well. However, there were still problems including lack of student interest, students' negative assumptions about Arabic, and students who were still at the level of reading (iqra'). Teachers' efforts in overcoming these problems included familiarizing students with the Arabic vocabulary (mufrodat) used in learning materials through the translating method and extra activities in the form of Foreign Language Development Programs.